State History. Sports, Cont'd Horse Racing Track. Horse Racing. (1937)
Hockey Leaders Are Defeated:Red And White Blanks Lang Stove As Silver Loaf Whips Coeur d'Alene. HOCKEY LEADERS ARE DEFEATED Red and White Blanks Lang Stove as Silver Loaf Whips Coeur d'Alene. The Red and White storemen and Silver Loafs bakers held the spotlight in the Big Four amateur hockey league this week' by virtue of clean-cut victories over Lang Stove and the Coeur d'Alene Eskimos in a pair of fast games at the ice arena last night. Red and White started the ball rolling by blanking the league leading Lang Stove crew, 2 to 0, in the opener, and Silver Loaf closed the evening with a 3-to-0 victory over the Lake city team. Storemen Have Edge. Lang Stove opened the first game with its usual fast, rough pace, but it was soon evident that Red and White had the best of things as far as passing and skating were concerned, despite the fact that neither team scored during the first period. Ken Henderson of the Eskimos went down after being hit above the eye by a flying puck to provide the main bit of excitement in the first period. The second session saw the two teams deadlocked in a futile bat-of play, when Loren Moffat, playtle until after about nine minutes inning an outstanding game for the storemen at center, took a pass Lang Stove goal and poked it in from Ken Mai mo in front of the for the first tally. The stovemen lost Jim Slawter on a penalty, but instead of stalling Ernie Harper made a single-handed drive which nearly ended in a score. Elmer Jackson, shifty little Red and White goalie, saved the day as he slapped the puck on past the mouth of the net. Breen Stops Threat. Andy Simchuck nearly scored for the storemen and after Goalie Neil Breen had stopped a scoring play by Loren Moffat and Jack Terris, the period ended without further scoring. As the final session opened, Dick Farrel, one of the leaders of the Red and White offense, nearly completed a neat scoring play by Andy Simchuck and Jack Terris. A moment later, the Red and White forward wall swept down the ice again and Jack Terris took the puck from Andy Simchuck and slipped it past Goalie Neil Breen for a clean score. Goalies Work Hard. The remainder of the third period was a fight to the finish between the two teams, featuring several brilliant saves by both goalies and the first penalty for Red and White. Loren Moffat nearly scored again for the storemen when he took a pass from Ed Henderson near the Lang Stove goal, but his shot was too strong and lifted over the net. Lang Stove. Red and White. Neil Breen. . . . . G . . . . . . . . . . . Elmer Jackson Jim Slawter. . . . . . D. . . . . . . . . . . Hal Etter Dutch Alberthal . . . .D . . . . . . . . . L. MacKay Cy Steel. . . . . . . . . . C . . . . . . . . Andy Simchuck Ken Henderson. . . . . LW. . . . . . . . .Jack Terris Ernie Harper. . . . . . . RW . . . . . . . . . Dick Farrel Spares: Lang Stove—Glen Gillette, Bill Recor: Red and White—Don Harcey, Loren Moffat. Ed Henderson. First period: No scoring. Penalties— Ken Henderson. Second period: 1. (Red and White) Moffat (Malmo) 9:05. Penalties—Slawter. Third period: 2. (Red and White) J. Terris (Andy Simchuck) 2:20. Penalties—L. MacKay. The Silver Loaf-Coeur d'Alene Eskimo game was a one-sided affair, as the accurate long shots of the Lake city men were knocked down by Goalie Ray Breen of the, Bakers and Silver Loaf showed an improvement in passing and team play to punch over three scores.